Fraction collection of bioactive compounds from ion chromatography: No longer mission impossible - Hans S.A. Yates; James F. Carter; Mary T. Fletcher; Viviene S. Santiago; Ondrea Thompson; Natasha L. Hungerford (MethodsX)
This paper demonstrates the fraction collection of the novel sugar trehalulose, using a modified ion chromatograph. The Ion Chromatography (IC) method, previously published for the analysis of trehalulose, was augmented with a suppressor and purpose-made switching valve unit. A sample of stingless bee honey was then run, following the three main steps: • Separation of trehalulose fraction • Lyophilization • Confirmation of trehaluloseThe method should be applicable to not only sugar analysis but to any bioactive compound separable by IC. The authors were not able to find a similar method within currently published literature.